Existence result for variable exponents elliptic system with lack of compactness. Issue 6 (13th April 2022) - Saifia, Ouarda; Vélin, Jean
Abstract : In this article, we prove the existence of a solution for nonlinear system governed by ( p ( x ), q ( x ) ) -Laplacian operators by using the concentration-compactness Principle for recovering the lack of compactness and some variable techniques.